Odpowiedź:
zad 1
a)
a₂ = a₁ + r = - 3
a₅ = a₁ + 4r = - 24
układ równań
a₁ + r = - 3
a₁ + 4r = - 24
odejmujemy równania
a₁ - a₁ + r - 4r = - 3 + 24
- 3r = 21
3r = - 21
r - różnica ciągu = - 21/3 = - 7
a₁ + r = - 3
a₁ - wyraz pierwszy = - 3 - r = - 3 + 7 = 4
a₁₅ = a₁ + 14r = 4 + 14 * (- 7) = 4 - 98 = - 94
S₁₅ = (a₁ + a₁₅) * 15/2 = (4 - 94) * 7,5 = - 90 * 7,5 = - 675
b) ciąg geometryczny
a₂ = a₁q = - 3
a₅ = a₁q⁴ = - 24
a₅/a₂ = a₁q⁴/a₁q = q³
q³ = (- 24)/(- 3) = 24/3 = 8
q = ∛8 = 2
a₁q = - 3
a₁ = - 3/q = - 3 : 2 = - 3/2 = - 1 1/2 = - 1,5
S₁₅ = a₁(1 - q₁₅)/(1 - q) = - 1,5(1 - 2¹⁵)/(1 - 2) = - 1,5(1 - 32768)/(- 1) =
= 1,5 * (- 32767) = - 49150,5
zad 2
a)
(7 + 2 + 5 + 7 + x + 3 + 9 + 2)/8 = 6
(35 + x)/8 = 6
35 + x = 8 * 6 = 48
x = 48 - 35 = 13
b)
Szereg uporządkowany
2 , 2 , 3 , 5 , 7 , 7 , 9 , 13
me - mediana = (5 + 7)/2 = 12/2 = 6
c)
D - dominanta
D₁ = 2
D₂ = 7